Patellofemoral morphology and alignment: reference values and dose-response patterns for the relation to MRI features of patellofemoral osteoarthritis - Macri, E. M.; Felson, D. T.; Zhang, Y.; Guermazi, Ali; Roemer, Frank; Crossley, K. M.; Khan, K. M.; Stefanik, J. J. (Osteoarthritis and Cartilage, 2017)
We aimed to (1) determine reference values for trochlear morphology and patellofemoral (PF) alignment in adults without magnetic resonance imaging (MRI)-defined PF full thickness cartilage damage or knee pain; and (2) evaluate dose-response patterns for these measures with prevalent MRI-defined PF structural damage and/or knee pain.The Framingham Community Cohort is a population-based sample of ambulatory adults aged >=50 years. We evaluated six morphology and alignment measures using MRI (n = 985), and reported reference values (mean ± 2SD) in a subsample without MRI-defined PF full thickness cartilage damage or knee pain (n = 563). With restricted cubic spline Poisson regression, we evaluated dose-response patterns of each of the six measures with prevalent MRI-defined PF structural damage or joint pain. Our primary outcome was full thickness cartilage damage.For dose-response curves, prevalence ratios (PR) increased monotonically for all measures except patellar tilt, which rose with both lateral and medial tilt. Associations were generally strongest in the lateral PF compartment. PR for the strongest predictors of full thickness cartilage damage reached clinical relevance (PR > 1.5) at sulcus angle (SA) >=135.0°; patellar tilt angle at <=1.0° and >=15.0°; and bisect offset >=57.0%. Lateral trochlear inclination (LTI) achieved PR > 1.5 at <=23.0° for full thickness cartilage damage with pain.SA, patellar tilt, and bisect offset were most strongly associated with full thickness cartilage damage. LTI, patellar tilt and bisect offset had stronger associations with the addition of pain. These findings contribute to better identifying a subset of patients who may benefit from mechanically based interventions.
EVALuna2:14705